Underwater Cultural Heritage and Submerged Objects: Conceptual Problems, Regulatory Difficulties. The Case Of Spain (Spanish Yearbook of International Law, 2010)
The recent entry into force of the 2001 UNESCO Convention on the Protection of Underwater Cultural Heritage means certainly good news for the protection of this part of the legacy of past generations. A great deal still remains to be done, however. 2001 Convention has a limited personal and material scope of application. In its absence, the international regime applicable to this kind of heritage spreads out among a number of heterogeneous instruments focused on diverse topics. One of the problems that the said diversity and heterogeneity causes is the variety of terms and definitions used by it. On the other hand, the implementation of a series of instruments so different becomes particularly complex when referring to States that have partially transferred their competences “up” to a regional integration organization, like the European Union, and “down” to decentralized territorial units, like the so-called Autonomous Communities. To this respect, the case of Spain provides with a good example of such difficulties.